UrbanReleaf: Enhancing Sustainable Urban Transformation with a Data-Driven Solution for Smart Depaving - Morandi Santos, Rafaela; Sarmento, Lucas; Cazzolato, Mirela T.; de Arruda Leite, Harlei Miguel (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2025)
How does the proliferation of impervious surfaces affect the quality of life? Impermeabilization due to paving contributes to urban issues, such as increased temperatures, which form the so-called heat islands. It can also cause more intense and frequent floods, diminished biodiversity, and deterioration of air quality. In this context, depaving is a practical solution for increasing urban resilience. Given a large urban region covered by impervious surfaces, how can we select the best points for intervention? We propose the UrbanReleaf method to map excessively paved urban areas and simulate the environmental impact of implementing green infrastructure. UrbanReleaf identifies critical zones for nature-based interventions such as depaving and forecasts environmental outcomes, including surface temperature, soil moisture, and vegetation indices. The method achieves this by leveraging geospatial satellite imagery and machine learning regressors to analyze vegetation indices, land surface temperatures, and moisture content. Experimental results show that UrbanReleaf can support urban planners and policymakers with data-driven clues that can help mitigate problems caused by impermeabilized areas.